An Amish courtship on Ice Mountain - Long, Kelly (Zebra Books, Kensington Publishing Corp., 2017)
Nineteen-year-old caregiver Martha believes that Joel Umble, the future Bishop of Ice Mountain, is out of her league until a possible future with Joel is revealed to her in an unexpected way at the creek.